The analytical scoring assessment usage to examine Sundanese students’ performance in writing descriptive texts - Dedi Koswara; Ruswan Dallyono; Agus Suherman; Pandu Hyangsewu (LPMPP Universitas Negeri Yogyakarta, 2021)
Many scholars view writing as a highly laborious task because many subcomponents are to be moulded into a single discourse. This issue is also faced by Indonesian higher education students, particularly sophomore students of the department of Sundanese language education. Therefore, this present study aims to uncover the factual evidence of whether the use of a rubric can enhance valid judgment. This process employed a validity and reliability scoring system. Subsequently, it is also significant to examine the functions of a rubric to promote sophomores’ learning and develop instruction from lecturers in the department of Sundanese language education. This study objectively assesses students’ descriptive writing in Sundanese language by considering the analytical scoring assessment functions. It turns out that the outcomes motivated the lecturers to constantly simplify the criteria in order to fit sophomores' descriptive texts, discover significant features, and incorporate the qualities into their own text insights. Furthermore, depending on the text complexity, such as intermediate, pre-advanced, and advanced writing, as well as students' writing competence and maturation, lecturers may modify the analytical rubric that moderately recommends the necessary qualities of descriptive texts or encompasses a wider component of rubrics qualities. This finding implies that the analytical scoring rubric incorporates the influential scoring method into daily activities.